Access to Mobile Phones and Women's Socio-Economic Empowerment in Rural Areas of Bangladesh: Understanding Gender Relation Transformation - Shamim Noor; Morshadul Hoque (Universitas Djuanda, 2021)
The discussion about women's access to and use of ICTs in developing countries has been an unsettled issue. Some schools of thought claim that due to engagement with household chores, traditional social norms, and values, women are less interested in ICTs, while others argue that like other social products, technology is not gender-neutral. However, this research conducted an empirical study on the self-employed women in rural areas of the Chittagong District of Bangladesh. A mixed-method was applied to analyze the collected data. The study tries to explore the impact of mobile phones and mobile internet on rural women’s income generation activities; and how gender relation at the household level has been transforming due to access to mobile phones. The findings reveal that having access to mobile phones, rural self-employed women are performing better than women who have no access to mobile phones and mobile internet. From both social and economic perspectives, the uses of mobile phones assist rural women to take part in decision-making, awareness build-up, increase movement, and control over income. However, strong patriarchal norms and traditional cultural constraints sometimes create barriers in access to mobile phones for rural women. Notwithstanding, the study depicts that ensuring gender-sensitive ICT policy and social awareness activities might lessen the barriers of women’s access to mobile phones and the internet in the periphery areas. However, this research puts these issues to an empirical test.